Crossing the communication divide: Intergroup contact and the desire to learn the outgroup's language. Issue 4 (1st October 2016) - Joyce, Nick; Vincze, Laszlo; Marton, Eniko Julia
ABSTRACT: This paper explores the role of ethnolinguistic vitality and intergroup contact in changing attitudes and the interest to learn Hungarian among Slovak-speaking secondary school students in Southern Slovakia ( N = 225). Several indirect paths linking the all these variables were found. In general, lower local ethnolinguistic vitality of Hungarian decreased intergroup anxiety and increased the quality of contact with members of the Hungarian minority, which led to a more positive attitude toward the Hungarian minority, and enhanced the interest to learn Hungarian.